2015
DOI: 10.1007/s11661-015-3175-y
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Age-Hardening Model for Al-Mg-Si Alloys Incorporating the Room-Temperature Storage and Cold Deformation Process Stages

Abstract: In this article, a new age-hardening model for Al-Mg-Si alloys is presented (named NaMo-Version 2), which takes into account the combined effect of cold deformation and prolonged room-temperature storage on the subsequent response to artificial aging. As a starting point, the original physical framework of NaMo-Version 1 is revived and used as a basis for the extension. This is permissible, since a more in-depth analysis of the underlying particle-dislocation interactions confirms previous expectations that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 63 publications
(181 reference statements)
3
30
0
Order By: Relevance
“…Assuming the presence of the Sc,Zr-containing particles, it can also be concluded that the yield strength of the AlZnMgScZr alloys cannot be expressed as a linear superposition of several strength contributions. This conclusion is in agreement with the observation of the others in the commercial AA6xxx alloys, see [30,31]. The AlZnMgScZr alloys show significantly higher HV values at higher temperatures in contrast to the AlZnMg alloys ( Fig.…”
Section: Phase Development In the Heat-treated Alloys During Isochronsupporting
confidence: 92%
“…Assuming the presence of the Sc,Zr-containing particles, it can also be concluded that the yield strength of the AlZnMgScZr alloys cannot be expressed as a linear superposition of several strength contributions. This conclusion is in agreement with the observation of the others in the commercial AA6xxx alloys, see [30,31]. The AlZnMgScZr alloys show significantly higher HV values at higher temperatures in contrast to the AlZnMg alloys ( Fig.…”
Section: Phase Development In the Heat-treated Alloys During Isochronsupporting
confidence: 92%
“…Assuming the presence of the primary and secondary Al3(Sc,Zr)-phase particles it can be also concluded that the yield strength cannot be captured as a linear superposition of several strength contributions. This conclusion is in an agreement with other observations in commercial 2xxx, 6xxx and 7xxx alloys, see References [20,25,65,[67][68][69].…”
Section: Phase Development During Isochronal Annealingsupporting
confidence: 93%
“…These models include the Kocks-Mecking model [9][10][11], the Alflow model [12], and Myhr et al's model [13]. Although these sophisticated models may include the effects of stacking fault energy, grain size, impurity element content, precipitation particle sizes/contents, etc., on the hardening behavior of alloys, we elected to use a simpler Hollomon equation (σ t = Kε t n , where σ t , ε t , K, and n are true stress, true strain, strength coefficient, and strain hardening exponent, respectively) to represent the hardening behavior of Al-A319 alloys.…”
Section: Interrelated Mechanical Propertiesmentioning
confidence: 99%